2007
DOI: 10.4049/jimmunol.178.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of Murine Autoimmunity via Dominant Anti-Inflammatory Effects of Interferon γ

Abstract: There is a paucity of knowledge concerning the immunologic sequelae that culminate in overt autoimmunity. In the present study, we have analyzed the factors that lead to disease in the model of autoimmunity, murine experimental autoimmune encephalomyelitis (EAE). EAE in H-2u mice involves autoreactive CD4+ T cells that are induced by immunization with the immunodominant N-terminal epitope of myelin basic protein. The affinity of this epitope for I-Au can be increased by substituting lysine at position 4 with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 74 publications
2
35
0
Order By: Relevance
“…Therefore, to avoid immunologic exhaustion and to focus on the competitive activities among T cell clones, an eightfold lower amount of 25 μg was used for all subsequent APL immunizations. These results correspond with the findings that Ac1-9(Y4) induces severe EAE at low but not high concentrations (15).…”
Section: Resultssupporting
confidence: 79%
“…Therefore, to avoid immunologic exhaustion and to focus on the competitive activities among T cell clones, an eightfold lower amount of 25 μg was used for all subsequent APL immunizations. These results correspond with the findings that Ac1-9(Y4) induces severe EAE at low but not high concentrations (15).…”
Section: Resultssupporting
confidence: 79%
“…Thus, while low levels of IFN-␥ in DR3 mice are proinflammatory, high levels in DR3DQ6 mice are protective. Although IFN-␥ is considered a proinflammatory cytokine, the anti-inflammatory role of IFN-␥ is well-established (31)(32)(33)(34)(35)(36)(37). Genetic deletion of IFN-␥ or IFN-R gene caused exacerbation of EAE in a certain strain of mice (35,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the preservation of IFN-␥ production by 45D is highlighted by numerous studies revealing a protective, anti-inflammatory role of IFN-␥ in EAE (12)(13)(14)(15)(16)(17)(18)(19)(20). Moreover, it has been reported that the poor encephalitogenicity of a high-affinity myelin-associated MHC variant peptide can be reversed by anti-IFN-␥ Ab (30). Given the protective role of IFN-␥ in EAE and the ability of 45D to maintain IFN-␥ production by MOG-reactive CD4 ϩ T cells, we hypothesized that IFN-␥ was required to inhibit the responsiveness of myelin-reactive CD4 ϩ T cells to weak MHC variant peptides and thereby prevented the induction of EAE.…”
Section: Discussionmentioning
confidence: 99%